ANALISIS KUALITAS PELAYANAN ANGKUTAN YANG BERKELANJUTAN PADA DINAS PERHUBUNGAN KABUPATEN SUMEDANG - Arip Rahman Sudrajat; Tasya Andini Putri; Intan Nuryana; Dede Yanti; Eli Windi; Riska Ratna Sari (JRPA - Journal of Regional Public Administration, 2021)
This research aims to find out the quality of sustainable services in the field of transportation, by looking for data and objective information on the analysis of sustainable services in the Field of Transportation in Dinas Perhubungan Kabupaten Sumedang. The benefit of this research is to provide positive and constructive reference to practical problem solving related to the title of the research. The research method used is descriptive research using qualitative analysis study approach. Data collection techniques are literature studies, field studies (observations, interviews, and documentation). While the data processing procedure is used data analysis model Miles and Huberman. The informant in this study was determined using purposive sampling method of 3 people. The final results of this study concluded that the quality of sustainable transportation services in Dinas Perhubungan Kabupaten Sumedang has gone quite well but not yet maximal. It can be seen from several things, namely that the quality of service from employees is still not good, in this case employees have not been able to provide services in accordance with applicable standards, there are limitations and shortages of employees in the field of knowledge (when using technology). Therefore, the results of this research can be used as references and recommendations to support the quality of sustainable transportation services in Dinas Perhubungan Kabupaten Sumedang.